PERBANDINGAN ANTARA DESAINER INTERIOR DAN DEKORATOR INTERIOR - Giris Ngini (JURNAL PERSPEKTIF ARSITEKTUR, 2010)
The terms "interior designer" and "interior decorator" are often used interchangeably, as if they wereidentical professions. Although both may have the ability and talent to create beautiful rooms, the twoare not synonymous.Interior decorators are primarily concerned with surface decoration, generally refers to someone whodeals with finishes, surfaces, furniture, and wall coverings and no government regulation regarding thework of an interior decorator.On the other hand, an interior designer is one who is trained to create a functional and quality interiorenvironment, qualified through education, experience and examination, so a professional designer canidentify and creatively resolve issues and lead to a healthy, safe and comfortable physical environment.Referring to that definition, interior design is the art and science of understanding people's behaviorin order to create functional spaces within the building structures, an in the other hand, an interiordecoration is the art of decorating to beautify a space.Although an interior designer can also make aesthetic changes to an interior space, the interiordesigner is a professional licensed with a licensing authority who coordinates design projects with aholistic approach. This effort includes designing the interior architecture, in addition to beautifying thespace.